Enhancing biodegradable polymer surface wettability properties through atmospheric plasma treatment and nanocellulose incorporation - Shi, Shih-Chen; Hsieh, Chia-Feng; Rahmadiawan, Dieter (Jurnal Pendidikan Teknologi Kejuruan, 2024)
This study investigates the effects of atmospheric plasma treatment on the surface properties of polylactic acid (PLA)/nanocrystalline cellulose (CNC) composites, aiming to improve their wettability and mechanical properties. The research utilizes a twin-screw extrusion process for fabricating PLA/CNC biocomposites, followed by surface modification using a custom-built, with a tenfold high-voltage atmospheric plasma system. The motivation of this treatment was to improved surface wettability and potential for enhanced adhesive bonding in ecological applications. These findings contribute to developing more sustainable composite materials by providing a method to improve the functionality of biodegradable polymers without compromising their environmental benefits.